2022
DOI: 10.1038/s43705-022-00161-0
|View full text |Cite
|
Sign up to set email alerts
|

Iron-dependent mutualism between Chlorella sorokiniana and Ralstonia pickettii forms the basis for a sustainable bioremediation system

Abstract: Phototrophic communities of autotrophic microalgae and heterotrophic bacteria perform complex tasks of nutrient acquisition and tackling environmental stress but remain underexplored as a basis for the bioremediation of emerging pollutants. In industrial monoculture designs, poor iron uptake by microalgae limits their productivity and biotechnological efficacy. Iron supplementation is expensive and ineffective because iron remains insoluble in an aqueous medium and is biologically unavailable. However, microal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 95 publications
(124 reference statements)
0
6
0
Order By: Relevance
“…This decrease was attributable to the consumption of organic carbon, which served as an essential energy source and electron donor for S. microflavus in the removal of heavy metals . A mass balance evaluation revealed that more organic matter was consumed than required for V­(V) reduction, as the growth metabolism and biomass synthesis of S.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This decrease was attributable to the consumption of organic carbon, which served as an essential energy source and electron donor for S. microflavus in the removal of heavy metals . A mass balance evaluation revealed that more organic matter was consumed than required for V­(V) reduction, as the growth metabolism and biomass synthesis of S.…”
Section: Resultsmentioning
confidence: 99%
“…This decrease was attributable to the consumption of organic carbon, which served as an essential energy source and electron donor for S. microflavus in the removal of heavy metals. 53 A mass balance evaluation revealed that more organic matter was consumed than required for V(V) reduction, as the growth metabolism and biomass synthesis of S. microflavus necessitated an ample supply of carbon sources. 18 Over the course of V(V) reduction, biomass steadily increased, signifying the respiration of V(V) by S. microflavus via electron transfer.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The addition of Se increased the phycocyanin concentration of Arthrospira maxima from 226 to 274 mg L -1 which was 21.2% higher than that in the control group (Chen et al, 2006). Most studies on the influence of mineral elements on phycocyanin presently focused on a single factor, such as Ni, Ca and Fe (Sloth et al, 2006;Velu et al, 2019;Rawat et al, 2022;Yang et al, 2022), and showed a good effect on phycocyanin. Arthrospira requires a small number of mineral components to grow.…”
Section: Discussionmentioning
confidence: 99%
“…Siderophore-mediated iron chelation enhances the formation of bioavailable iron complexes, which algae can then absorb through plasma membrane-bound ferrireductase [ 128 ]. Consequently, the introduction of siderophore-producing Ralstonia pickettii establishes a mutualistic relationship whereby the bacteria benefit from the photosynthetically fixed algal exopolysaccharides while reciprocally enhancing the growth and degradation of complex azo dyes by C. sorokiniana [ 129 ].…”
Section: Terrestrial and Freshwater Microalgaementioning
confidence: 99%